Prediction of maximal oxygen uptake from submaximal and maximal exercise on a ski ergometer - Klusiewicz, A.; Faff, J.; Starczewska-Czapowska, J. (Biology of Sport, 2011)
The aim of the study was to assess the accuracy of prediction of maximal oxygen uptake ( VO2max) from submaximal and maximal exercises on a ski ergometer, which imitated the work of the arms during cross-country skiing. Twenty-seven female and twenty-nine male biathletes and cross-country skiers were investigated. The subjects performed the incremental exercise test on the ski ergometer until volitional exhaustion. VO2max was determined directly and its predicted values were calculated from the linear relationship between VO2 and HR in a submaximal exercise extrapolated to the age-predicted HRmax; from the linear relationship between VO2 and power output at submaximal and maximal exercise; from the linear relationship between VO2max and VO2 at HR=170/min and from the linear relationship between VO2max and power output at HR=170/min. The differences between measured and predicted VO2max ranged from 0.3% to 1.2% (NS). Correlation coefficients between measured and predicted VO2max ranged from 0.6 to 0.91 (p<0.001). Total error ranged from 5.91% to 11.7% and standard estimation error from 5.3% to 11.0%. The results demonstrated that VO2max can be predicted from the exercise test on the ski ergometer both in the submaximal exercise from the relation between heart rate and oxygen uptake or power output and from the relation between VO2max and maximal power output without oxygen uptake measurement.